Development of a methodological framework for assessing the resilience of socio-economic systems in the context of sustainable development - Savytska, Nataliia; Pakhucha, Ellina; Sawicka, Janina; Olinichenko, Kateryna; Mykhailova, Mariia; Polevych, Andrii (Technology audit and production reserves, 2025)
The object of research is the methodological foundations for assessing the level of resilience of the socio-economic system in the context of sustainable development management. The main problem focused on in the research is determining the economy's ability to adapt to external and internal shocks in order to minimise their impact and ensure sustainable development. The proposed macroeconomic resilience index (MRI) is constructed using content analysis, systemic, index and quantitative approaches. The developed system for assessing the macroeconomic resilience index covers 18 indicators, which are grouped into four dimensions of resilience: economic, environmental, social and institutional. A sub-index is calculated for each dimension, which allows for a decomposition analysis of the adaptive potential of each area of management. The proposed four-level scale for assessing the resilience of the socio-economic system allows for a quantitative assessment of its state and the identification of vulnerable areas of management. The scale defines a specific state of the system: critical vulnerability; fragile adaptability; moderate; adaptive, and systemic resilience. The use of the macroeconomic resilience index (MRI) methodology allows assessing the ability of the socio-economic system to adapt, recover and maintain viability in crisis conditions. Applying the proposed methodology to assess Ukraine's case in the period 2019–2023, it was found that the socio-economic system on the resilience scale ranges from a state of vulnerability MRI = 0.26 to adaptive resilience MRI = 0.68. It has been established that the social and environmental spheres are critically vulnerable areas for the recovery of the socio-economic system. Meanwhile, the economic and institutional spheres formed the foundation of the resilience of the Ukrainian macroeconomy. The proposed assessment system provides a basis for developing practical recommendations for strengthening adaptive capacity and supporting the resilience and sustainability of socio-economic systems.